Seeing-in is no seeing-through - Voltolini, Alberto (Rivista Italiana di Filosofia del Linguaggio, 2017)
In this paper I intend to focus on the transparency account of picture perception, according to which picture perception is, in many cases at least, a species of perception of transparency that displays a transparency effect even in absence of physical transparency. Basically, I want to show that this account is not correct. For not only it does not rightly capture the phenomenology of picture perception, but also, and more importantly, it does not explain that perception, since picture perception is necessary for a transparency effect. Yet this criticism does not altogether intend to deny that, as to picture perception, the transparency account has some insights that must be kept in any good account of such a perception: namely, the fact that picture perception involves an element of aware illusoriness and the fact that it brings in a sort of transfiguration of the pictorial vehicle per se, the physical basis of a picture, into something that has a pictorial value.